Ketidaksetaraan Gender dalam Hukum Pidana: Analisis Terhadap Dampak dan Solusi - Afinda Wahyu Nur Sholikhah (JOURNAL SAINS STUDENT RESEARCH, 2024)
Gender inequality in the context of criminal law is a problem that requires in-depth understanding and concrete solutions. This research aims to identify abstract forms of gender inequality in criminal law, evaluate their impact on society, and present solutions that can provide a foundation for more inclusive reform. This study uses a legal and gender analysis approach to reveal forms of gender inequality, including disparities in the definition of crime and the application of sanctions. The results of the analysis show that there are gender stereotypical views that influence the judicial process. The impact of gender inequality in criminal law can be seen through unequal access to justice, limited fulfillment of human rights, and limited participation of women in the legal system. In this context, this research strengthens the urgency of change to create a criminal law system that is fairer and more equal. The proposed solution involves legislative reform to eliminate inequalities in the definition of crimes and the application of sanctions. In addition, training for legal actors is expected to reduce inequality in the judicial process. Community advocacy and women's empowerment are also considered crucial in overcoming gender stereotypical views. This article concludes that a deeper understanding of gender inequality in criminal law is an important first step. By responding holistically to its impacts, including through changes in legislation and changes in societal attitudes, we can build the foundations for a criminal justice system that is fairer, more equitable and meets human rights principles.